Uncertainty about average profitability and the diversification discount - Hund, John; Monk, Donald; Tice, Sheri (Journal of Financial Economics, 2010)
The diversification discount (multiple segment firm value below the value imputed using single segment firm multiples) is commonly thought to be generated by agency problems, a lack of transparency, or lackluster future prospects for diversified firms. If multiple segment firms have lower uncertainty about mean profitability than single segment firms, rational learning about mean profitability provides an alternative explanation for the diversification discount that does not rely on suboptimal managerial decisions or a poor firm outlook. Empirical tests which examine changes in firm value across the business cycle and idiosyncratic volatility are consistent with lower uncertainty about mean profitability for multiple segment firms.